Regulação da expressão da anexina A1 e sua ação modulatória em processos inflamatórios e infecciosos in vitro e in vivo - Priuli, Angela Aparecida Servino de Sena (2012)
Background: Exacerbated or prolonged inflammatory responses can be detrimental to the host, then any antiinflammatory mediators act to regulate the properties of pro-inflammatory factors and ensure the homeostasis of the organic systems. Objectives: Aims: This study has focused in the regulation of expression and the immunomodulatory properties of annexin A1, a protein of 37 KDa, originally known as the second messenger action of glucocorticoids, in inflammatory and infectious processes. Methods: Using molecular (qPCR), biochemical (luminometry) and immunological (flow cytometry, immunofluorescence) tools, we investigated the endogenous and exogenous of ANXA1 and its mimetic peptide (Ac2-26) in different conditions in vitro and in vivo: fungi infection, HIV/SIV infecion, bowel inflammatory disease and renal ischemic injury. Results: The Ac2-26 pre-treatment of PMN and PBMC of human peripheral blood stimulated with opsonized-zymosan inhibited the production of reactive oxygen species in a dose-dependent manner. In parallel, incubation of phagocytes with the peptide was shown to decrease expression of TLR2 receptor, responsible for the recognition of zymosan on phagocyte, suggesting a regulatory mechanism of surface receptor by ANXA1 peptide. Due to last data, the expression of CCR5, chemokine receptor and HIV co-receptor, was investigated in the same in vitro conditions. CCR5 transcription was down-regulated in PBMC from HIV-infected and healthy subjects, partially by ANXA1/FPR pathway. Consistently, both PBMC subject groups showed an impairment of percentage of CCR5+CD4+ T cells after Ac2-26 incubation. In contrast, Ac2-26 showed an up-regulation of CCR5 surface expression in monocytes, however the peptide switched the profile of monocyte subsets, increasing CD14highCD16- and decreasing CD14lowCD16+ populations. The last one is the most susceptible to HIV infection. In conclusion, the data suggest that the action of N-terminal ANXA1 is cell-dependent and may contribute indirectly modulating the HIV-1. Coherently, the study in vivo of ANXA1 expression in a non-human model of AIDS, showed that ANXA1 is regulated during the progression of the disease in the main compartments of infection, the blood and the gut. In comparison with samples of uninfected animals, the ANXA1 transcripts in peripheral blood increased from acute to chronic SIV infection, whereas in the intestinal mucosa it was down-regulated, reaching baseline levels only in chronic infection. Analysis of typical markers of AIDS progression, showed that increased ANXA1 transcripts was significantly correlated with the activation of T cells. However, the expression of ANXA1 had a positive correlation with antiinflammatory cytokines in the blood and in the intestine and a inverse dynamics of viral load and depletion of CD4 T cells, suggesting that activation of its transcription is related to an attempt to reduce the immune depletion during infection. In addition, based on the described differential modulation of the ANXA1 in the gut of primates, another goal was to analyze the expression of ANXA1 in patients with IBD (inflammatory bowel disease) or not treated with immunosuppressive drugs. The correlation among those factors and clinical data were analyzed. In IBD patients, the expression of ANXA1 is reduced in level of mRNA in peripheral blood and protein in the colonic mucosa. In these patients, immunotherapy with infliximab (anti-TNF-alpha) modulates the transcription of ANXA1 and TNF-α, and even systemic lymphocyte activation in accordance with the duration of treatment and the side effects of drugs, such as bacteremia. The dynamics of ANXA1 added to other clinical and immunological factors appear to be associated with the course of IBD. Finally, acute and chronic inflammatory process induced by ischemia/reperfusion (I/R) procedure, revealed that exogenous ANXA1 mimetic peptide granted a remarkable protection against kidney I/R injury, preventing glomerular filtration rate and urinary osmolality decreases and acute tubular necrosis development by affording striking structural protection due to the abortion of neutrophil extravasation, attenuation of macrophage infiltration and regulation of endogenous annexin A1 expression in renal epithelial cells. Conclusions: In a general analysis of all studies presented, we conclude that exogenous ANXA1 and its derived peptides act as key molecules in the modulation of specific activation, immunophenotype and distribution of phagocytes and lymphocytes participating as a line of defense or targeting of infectious agents, via FPRs or not. And, emphasizing the importance of ANXA1 in the defense of homeostasis, although it was found that the pathways related to the regulation of endogenous ANXA1 is differentially activated in tissues and fluids under acute and chronic inflammation caused by viral infection, autoimmunity or hypoxia.